25th Years Faculty of Medicine and Health Sciences:Forging Ahead: 25 Years of Diligence, Faith and Commitment - Rasidah, Abd Wahab (Unimas Publisher, 2022)
This is a coffee table book featuring 25th years of the Faculty of Medicine and Health Sciences achievement. The book contents history of the faculty, teaching and learning activities, research and partnership, community engagement, and outstanding clinical services offered by the faculty clinician. The book also showcase faculty special contribution in controlling Covid-19 and The UNIMAS Teaching Hospital Project.